GE_GERICHTE P/7890/2015 vom 28. September 2022 - GE Cour de justice (2022)
FAUX INTELLECTUEL DANS LES TITRES;AYANT DROIT ÉCONOMIQUE;FORMULE OFFICIELLE;TRUST;NÉGLIGENCE;CONVENTION DE DILIGENCE;BANQUE | CP.251; CPP.325; CPP.389; CPP.9; LBA.4